2016
DOI: 10.18052/www.scipress.com/ilns.59.82
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Spent Engine Oil Contaminated Soil by Using Fungus, <i>Penicillium sp.</i>

Abstract: Abstract. This study investigated the ability of Penicillium sp. to bio-remediate spent engine oil contaminated soil both in vitro and in vivo. In the in vitro assay, mycelium of a seven day old culture of Penicillium sp. grown on Sabouraud Dextrose Agar (SDA) was punched out using a 0.5mm Cork borer and inoculated on the centre of Petri dishes containing the spent and unspent engine oil and incubated for seven days and daily reading of the mycelia growth obtained using a metre rule. For the in vivo assay, soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Many researchers confirmed that the diversity of the fungal community is dominant among other inhabitants in the oil contamination of soils. Apparently, Aspergillus and Penicillium are the most common species in high oil-contaminated soils [53][54][55][56]. The study of actinomycetes showed that this group did not contain a large species diversity, and the group was mainly represented by the Cinereus section of the genus Streptomyces, in a minor amount.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers confirmed that the diversity of the fungal community is dominant among other inhabitants in the oil contamination of soils. Apparently, Aspergillus and Penicillium are the most common species in high oil-contaminated soils [53][54][55][56]. The study of actinomycetes showed that this group did not contain a large species diversity, and the group was mainly represented by the Cinereus section of the genus Streptomyces, in a minor amount.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that the increase in TOC of oil-polluted soil was observed to correspond with the increase in O&G content. 26,51,52) On the aspect of nitrogen contents, it was observed that the nitrogen content of soil increased with increase in oil contamination levels. The nitrogen content of the control soil was 2.4 mg/kg (0.24%), which was lower relative to the contaminated soils whose values were 3.6 mg/kg (0.36%) and 3.8 mg/kg (0.38%) for 5 and 10% oil pollution levels, respectively.…”
Section: Microbiological and Physicochemical Characteristics Of Soil Samplesmentioning
confidence: 99%
“…Contaminants build up in the soil, are absorbed by plant roots, seep into surface and ground water, and disperse as aerosolized pollutants into the air, all of which are harmful to human and animal health (Ghaemi et al, 2015;Edyta and Dariusz, 2020). Contaminants such as petroleum hydrocarbons and heavy metals are extremely harmful to the environment, and human exposure to these dangerous substances can have serious health repercussions as well as change the socioeconomic activities of a community (Umana et al, 2016;Aniefiok and Udo, 2019).…”
Section: Introductionmentioning
confidence: 99%